Are treatments effective for youth with anxiety disorders? : a meta-analysis : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - McMurray, Kirsten (Massey University, 2003)
Anxiety disorders are a disabling and enduring problem for a significant number of children and adolescents. Research in New Zealand has indicated anxiety disorders in adolescence are associated with anxiety, depression, substance dependence and academic underachievement later in life (Woodward & Fergusson, 2001). The purpose of this study was to examine the effectiveness of cognitive-behavioural treatments for childhood anxiety disorders. An additional aim was to establish the clinical significance of treatment outcomes. The design used was a meta-analysis. Seventeen outcome studies were identified for inclusion dating back to 1970, with a sample of 984 child participants, all diagnosed with a primary anxiety disorder. Though not one of the inclusion criteria, all studies employed behavioural or cognitive-behavioural approaches to treatment. Results indicated treatments were successful in alleviating anxiety symptoms and disorders as well as related areas of functioning. Overall findings indicated the average treated child was 79% more improved than untreated children or those treated with attention placebo conditions. Results also indicate that treatment effects are maintained across studies at various follow-up intervals. Moderator analyses suggested treatments to be effective for a range of anxiety disorders. Methodological limitations are identified and suggestions are made regarding future research. The relevance and application of the findings to the New Zealand context are considered.
Keywords: Anxiety -- Treatment -- Evaluation; Cognitive therapy -- Evaluation; Adolescent psychotherapy -- Evaluation